Penyelesaian Positif Model Penyebaran Virus Ebola Antar Dua Wilayah - Awawin Mustana Rohmah; Dinita Rahmalia (Jurnal Matematika, 2020)
A Model describing the epidemic spread of the Ebola virus disease in region 1 and region 2 can be formed in a mathematical model, one of which is the SEIR endemic model. To form a mathematical model it is necessary to know the phenomenon of the spread of the Ebola virus, namely the large number of infected populations in an area which is not only caused by infected individuals in one area but can be caused by individuals traveling from one region to another. In this case, the SEIR model is analyzed for existence and uniqueness. Before doing the Analyze, the SEIR model was simplified. Then lipschitz was determined, so that an analysis of existence and uniqueness could be carried out. This shows that the SEIR model has a unique solution. Furthermore, a positive solution is determined in the model, to show that the SEIR model has a continuous and dynamic flow. Based on these results, it was found that the SEIR model in the spread of the Ebola virus had dynamic and a continuous flow.